Konsep Beauty Privilege Dalam Persepektif Misbah Musthofa: (Studi Kajian Tokoh Terhadap Ayat-Ayat Kesempurnaan Manusia) - Fathul Falaah Al Akbar; Ikhwanudin; Muhammad Nur Amin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Over the years, humans have made major changes in various aspects of their lives, one of which is the concept of beauty. “Beauty” has become an important element in human life and is considered to have a major influence on social interactions. Most Indonesians assume that being beautiful will bring “privilege” to their lives. This study states that “Beauty Privilege” is an issue in society where those who have beauty in the form of a beautiful or handsome face, tall body, brown skin, and follow the criteria of beauty in the community will be treated special. This study uses Abdul Mustaqim's character research method. This study is also included in the type of library research (literature) by collecting scientific literature data from tafsir books, books, and journal articles. With the book of Tafsir Al-Iklīl fī ma'āni Al-Tanzīl by Misbah Musthofa, this research is focused on knowing Misbah Musthofa's opinion about vulnerability in his interpretation of the verses of human perfection. The explanation of Tafsir Al-Iklīl fī ma'āni Al-Tanzīl emphasizes the true meaning of vulnerability in Islam.